Proses Penghasilan Kitin daripada Kulit Udang - Wan Daud, Wan Ramli; Govindasamy, Parathan (1990)
Chitin is produced from prawn shells by removing protein and calcium carbonate. This production process is not well understood and is not amenable to mathematical modelling normally applicable to other chemical processes. The main aim of the present study is to identify process variables such as particle size, concentration of NaOH solution, temperature and protein removal time, concentration of HCl acid, temperature and chalk removal time which have significant effect on the chitin content (an indicator for chalk removal) and nitrogen (an indicator for protein removal) in the product. Factor analysis method is used. This study found that NaOH concentration, temperature and protein removal time affect the protein removal rate whereas the effect of particule size nonexistent. HCl concentration, temperature and chalk removal time are found to affect the chalk removal process. Linear models have been proposed for both cases by using the linear regression method. This process is currently being optimized in a further study.